2021
DOI: 10.1142/s0218202521500561
|View full text |Cite
|
Sign up to set email alerts
|

Where to cut to delay a pandemic with minimum disruption? mathematical analysis based on the SIS model

Abstract: We consider the problem of modifying a network topology in such a way as to delay the propagation of a disease with minimal disruption of the network capacity to reroute goods/items/passengers. We find an approximate solution to the Susceptible-Infected-Susceptible (SIS) model, which constitutes an upper bound to its exact solution. This upper bound allows direct structure-epidemic dynamic relations via the total communicability function. Using this approach we propose a strategy to remove edges in a network t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…This expression is known as the communicability function of a graph ( 26 , 27 ). While originally being a purely combinatorial expression that encapsulates the contributions of different walks in a graph, indeed emerges as a central matrix when analyzing a wide variety of dynamics on graphs ( 27 – 31 ) (see SI Appendix , S1.1 for details and S1.2 for a derivation of as the actual propagator in a specific case with Hamiltonian dynamics). Nowadays communicability is applied across a range of disciplines, from neuroscience ( 32 39 ) or cancer research ( 40 ) to ecology ( 41 ) or economics ( 42 ), to cite a few.…”
Section: Resultsmentioning
confidence: 99%
“…This expression is known as the communicability function of a graph ( 26 , 27 ). While originally being a purely combinatorial expression that encapsulates the contributions of different walks in a graph, indeed emerges as a central matrix when analyzing a wide variety of dynamics on graphs ( 27 – 31 ) (see SI Appendix , S1.1 for details and S1.2 for a derivation of as the actual propagator in a specific case with Hamiltonian dynamics). Nowadays communicability is applied across a range of disciplines, from neuroscience ( 32 39 ) or cancer research ( 40 ) to ecology ( 41 ) or economics ( 42 ), to cite a few.…”
Section: Resultsmentioning
confidence: 99%
“…While originally being a purely combinatorial expression that encapsulate the contributions of different walks in a graph, G(β) indeed appears as a central matrix when analysing a wide variety of dynamics on graphs: in Hamiltonian dynamics, G(β) corresponds to the thermal Green's function of a network of coupled quantum harmonic oscillators [17], and similarly, the so-called self-communicability term G ii (β) quantifies the probability of finding a network, represented by a tight-binding Hamiltonian, in a state with energy E j = −λ j at inverse temperature β [18]. In the context of epidemic processes, G(β) appears in the solution of a linearised upper bound to the susceptible-infected (see SI S1.1) and susceptible-infectedsusceptible models [19,20]. G(β) has also been recently shown to be the the solution a modification of the Kuramoto model [21].…”
Section: The Concept Of Resistive Pathsmentioning
confidence: 99%
“…The problem of modifying a network topology in such a way as to delay the propagation of a disease with minimal disruption of the network capacity to reroute goods/items/passengers is considered here in 6 . A strategy is developed to remove edges in a network and it is shown that this significantly delays the propagation of a disease across the network with minimal disruption of its capacity to deliver goods/items/passengers.…”
Section: Presentation Of the Special Issuementioning
confidence: 99%